Scaling children's waist circumference for differences in body size. Issue 6 (12th July 2017) - Nevill, Alan M; Duncan, Michael J.; Lahart, Ian M; Davies, Paul; Ramirez‐Velez, Robinson; Sandercock, Gavin
Abstract: Objectives: Both waist circumference (WC) and body size (height) increase with age throughout childhood. Hence, there is a need to scale WC in children to detect differences in adiposity status (eg, between populations and different age groups), independent of body size/height. Methods: Using two culturally different samples, 1 English (10–15.9 years n  = 9471) and 2 Colombian (14–15 years, n  = 37, 948), for WC to be independent of height (HT), a body shape index was obtained using the allometric power law WC =  a .HT b . The model was linearized using log‐transformation, and multiple regression/ANCOVA to estimate the height exponents for WC controlling for age, sex, and any other categorical/population differences. Results: In both samples, the power‐law height exponent varied systematically with age. In younger children (age 10–11 years), the exponent was approximately unity, suggesting that pre‐pubertal children might be geometrically similar. In older children, the height exponent declined monotonically to 0.5 (ie, HT 0.5 ) in 15+ year‐olds, similar to the exponent observed in adults. UK children's height‐adjusted WC revealed a "u" shaped curve with age that appeared to reach a minimum at peak‐height velocity, different for boys and girls. Comparing the WC of two populations (UK versus Colombian 14–15‐year‐old children) identified that the gap in WC between the countries narrowed considerably after scaling for height. Conclusions: Scaling children's WC for differences in height using allometric modeling reveals new insights into the growth and development of children's WC, findings that might well have been be overlooked if body size/height had been ignored.